High‐order dual‐band superconducting filter with independently controllable passbands and wide stopband. Issue 5 (25th March 2018) - Lu, Xinxiang; Guo, Xubo; Luo, Chenjie; Wei, Bin; Zhang, Liuwan; Cao, Bisong
Abstract: A stepped‐impedance‐stub loaded stepped‐impedance resonator (SISLSIR) is proposed to design a dual‐band bandpass filter. The even‐ and odd‐mode frequencies and the coupling strength of the proposed resonators can be independently designed and adjusted. A dual‐feedline structure is used to meet the required external couplings of the 2 passbands. Thus, both the center frequencies and the bandwidths of the 2 passbands can be independently controlled. A 6‐pole dual‐band filter with the passbands of 3300∼3600 MHz and 4800∼5000 MHz is successfully designed using the proposed method and fabricated with YBCO/MgO high‐temperature superconducting (HTS) wafer. The measured results of the filter exhibit high performance and match well with the simulations. The measured insertion losses are less than 0.2/0.3 dB, and the return losses are greater than 15/14 dB for the lower/upper passbands, respectively. The out‐of‐band rejection is greater than 68 dB up to 12 GHz.